The Effect of Financial Literacy on the Intention to Use Peer-to-Peer (P2P) Lending (Case Study of MSMEs Assisted by Rumah Berdaya Cilegon) - Nuresa, Difa; Fauziyah, Azizah; Rachmani, Nizza Nadya (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Fintech peer-to-peer lending has become a popular alternative source of business funding for MSMEs, but its use is not matched by adequate financial literacy skills. The purpose of this study is to determine the effect of financial literacy on the intention to use peer-to-peer lending among MSMEs under the guidance of Rumah Berdaya Cilegon. This study uses an explanatory quantitative approach. The sampling technique uses probability sampling, and the application of the Slovin formula results in a sample size of 77. Data were collected through questionnaires and analyzed using descriptive analysis, classical assumption tests, simple linear regression analysis, T-tests, and coefficient of determination tests. The results of the study indicate that financial literacy has a positive and significant effect on the intention to use peer-to-peer lending.